2016
DOI: 10.14710/jitaa.41.3.153-160
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Curcumin and Monochromatic Light in Improving Liver Functions of Sexually Mature Magelang Ducks

Abstract: Hati unggas betina memiliki peran vital sebagai tempat biosintesis prekursor kuning telur, karena perannya ini hati mudah mengalami kerusakan seluler. Tujuan penelitian ini ialah mengkaji efikasi suplementasi kurkumin dan penggunaan cahaya monokromatik dalam menekan histopatologi hati pada biosintesis kuning telur itik lokal. Pada penelitian ini digunakan seratus sembilan puluh dua ekor itik magelang betina. Rancangan penelitian yang digunakan ialah rancangan acak lengkap dengan susunan faktorial 4x4. Faktor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The plasma lipid concentration increased from 3 mg ml -1 in un-laying turkeys to 21 mg ml -1 during laying period (Bacon et al, 1974). Our previous study also found the increased serum vitellogenin (Kasiyati et al, 2016a) and fat droplet in hepatocytes vacuoles of magelang ducks supplemented with curcumin in exposed to white, red, green, or blue light (Kasiyati et al, 2016b).…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…The plasma lipid concentration increased from 3 mg ml -1 in un-laying turkeys to 21 mg ml -1 during laying period (Bacon et al, 1974). Our previous study also found the increased serum vitellogenin (Kasiyati et al, 2016a) and fat droplet in hepatocytes vacuoles of magelang ducks supplemented with curcumin in exposed to white, red, green, or blue light (Kasiyati et al, 2016b).…”
Section: Introductionsupporting
confidence: 63%
“…Optimized lipids catabolism increase substrate supply for the biosynthesis of yolk egg precursors. Curcumin supplementation of sexually mature female magelang ducks was closely related with the role of curcumin as hepatoprotector (Kasiyati et al, 2016b), supported by the use of monochromatic light can stimulate secretion of lipolytic hormones so the lipids were (Ke et al, 2011), so that biosynthesis of the egg yolk component in the liver cells more optimal. The liver of laying birds during sexual maturity have a great capability in converting lipids into the egg yolk component and directly taken by the plasma to be deposited into the growing ovarian follicle oocytes.…”
Section: Serum Triglyceride and Cholesterol At Sexual Maturity Of Magmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to the presence of estradiol, the physiological state of the liver has a major influence on vitellogenin synthesis (Kasiyati et al, 2016b). However, the supplementation of curcumin not only protects the liver cells but also increases their bioactivities as phytoestrogen that binds to the estradiol receptor and further stimulates the synthesis of vitellogenin (Kasiyati et al, 2016a;Dewi et al, 2018b). Research conducted by Turker and Bozcaarmutlu (2009) showed that feed containing high levels of phytoestrogens could increase vitellogenin production in carp.…”
Section: Discussionmentioning
confidence: 99%
“…Saraswati et al (2013) showed that the increase in turmeric powder supplementation up to 54 mg/quail/day showed the optimal results in improving the physiological conditions of quails. The bioactive Component of curcumin is very important as a hepatoprotector to protect hepatocytes from destruction caused by the free radicals, as was indicated by the decrease in the serum SGPT and SGOT concentrations in the ducks supplemented with curcumin (Kasiyati et al 2016). Figure 1.…”
mentioning
confidence: 99%